Amazonia Seasons Have an Influence in the Composition of Bacterial Gut Microbiota of Mangrove Oysters (Crassostrea gasar) - Conceição, Marcos Vinícius Reis; Costa, Sávio Souza; Schaan, Ana Paula; Ribeiro-dos-Santos, Ândrea Kely Campos; Silva, Artur; das Graças, Diego Assis; Schneider, Maria Paula Cruz; Baraúna, Rafael Azevedo (Frontiers in Genetics, 2021)
The mangrove oysters (Crassostrea gasar) are molluscs native to the Amazonia region and their exploration and farming has increased considerably in recent years. These animals are farmed on beds built in the rivers of the Amazonia estuaries and, therefore, the composition of their microbiome should be directly influenced by environmental conditions. Our work aimed to evaluate the changes in bacterial composition of oyster’s microbiota at two different seasons (rainy and dry). For this purpose, we amplified and sequenced the V3-V4 regions of the 16S rRNA gene. Sequencing was performed on the Illumina MiSeq platform. According to the rarefaction curve, the sampling effort was sufficient to describe the bacterial diversity in the samples. Alpha-diversity indexes showed that the bacterial microbiota of oysters is richer during the rainy season. This richness is possibly associated with the diversity at lower taxonomic levels, since the relative abundance of bacterial phyla in the two seasons remained relatively constant. The main phyla found include Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria. Similar results were found for the species Crassostrea gigas, Crassostrea sikamea and Crassostrea corteziensis. Beta-diversity analysis showed that the bacterial composition of oyster’s gut microbiota was quite different in the two seasons. Our data demonstrate the close relationship between the environment and the microbiome of these molluscs, reinforcing the need for conservation and sustainable management of estuaries in the Amazonia.